Problems of automating the use of land resources by local government under martial law (Моделювання, керування та інформаційні технології, 2025)
This article examines the challenges  related to the automation of land resource management by local government during martial law in Ukraine. The war has led to the suspension of many land operations, the closure of electronic services, and difficulties in accessing data from the State Land Cadastre. In addition, there have been issues with communication between authorities, limited access to information on land plots, technical difficulties, and financial constraints that complicate land resource management projects. Militaryactions have also caused land contamination, requiring additional measures for their restoration. The author emphasizes the need for a comprehensive approach to solving these problems through close cooperation between different levels of government and the use of modern technologies to overcome existing obstacles